N=2 superconformal description of superstring in Ramond-Ramond plane wave backgrounds - Berkovits, N.; Maldacena, J. (Int School Advanced Studies, 2002)
Using the U(4) formalism developed ten years ago, the worldsheet action for the superstring in Ramond-Ramond plane wave backgrounds is expressed in a manifestly N = (2, 2) superconformally invariant manner. This simplifies the construction of consistent Ramond-Ramond plane wave backgrounds and eliminates the problems associated with light-cone interaction point operators.
Keywords: superstrings and heterotic strings; Penrose limit and pp-wave background